Key Success Factors in Faculty Professional Development Programs - Afam Uzorka; David Makumbi (Journal of Research in Education and Pedagogy, 2026)
Faculty Professional Development (FPD) plays a critical role in enhancing teaching effectiveness, strengthening academic capacity, and fostering a culture of continuous learning in higher education institutions. However, across many African university contexts, FPD initiatives remain fragmented, under-resourced, and weakly aligned with faculty needs and institutional priorities. This study examined the key success factors that enable effective and sustainable faculty professional development programs within Ugandan universities. Using a qualitative descriptive research design, data were collected through semi-structured interviews with fifty-six participants, comprising faculty members and administrators drawn from ten public and private universities across four regions of Uganda. The data were analyzed using thematic analysis supported by NVivo 12 software. The findings revealed seven interrelated success factors underpinning effective FPD programs: institutional commitment and support; relevance and customization of program content; continuous and comprehensive learning opportunities; active learning and participant engagement; peer collaboration and professional networking; integration of technology; and systematic evaluation for continuous improvement. These factors explain how institutional alignment, participatory program design, and sustained support mechanisms enhance faculty motivation, skill acquisition, and long-term professional growth. The findings were synthesized into a context-sensitive conceptual framework grounded in adult learning theory and organizational support theory, illustrating interactions between institutional structures and individual learning processes. This study contributes original empirical evidence to the literature on faculty professional development in African higher education. It offers practical implications for university leaders and policymakers seeking to design responsive, inclusive, and sustainable professional development systems. Although situated in Uganda, the findings provide transferable insights to comparable resource-constrained contexts.